Strategi Dunia Usaha dan Bisnis Dalam Era New Normal - EDWIN ZUSRONY; WREDA AGUNG KUNCORO; Jaelani Jaelani (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2022)
World economic conditions changed in early 2020, where the Covid-19 pandemic made several countries in the world experience recession. Indonesia has also experienced the impact of the Covid-19 pandemic, especially small businesses or SMEs which are the main pillars of the national economy. The community service webinar entitled business and business dynamics in the new normal era is expected to provide an overview for employers as well as workers or employees who have experienced termination of employment and can take various business opportunities that can be used as solutions to survive. Community service activities in the form of webinars were attended by up to 350 participants from various elements such as entrepreneurs, academics, students, and the general public. The resource persons consisted of four people with backgrounds of entrepreneurs, professionals and academics who provided material exposures about the business world in the era of the Covid-19 pandemic.